2001
DOI: 10.1103/physrevlett.87.135002
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the “Self-Healing” of an Error Field Island in the Large Helical Device

Abstract: It was observed that the vacuum magnetic island produced by an external error magnetic field in the large helical device shrank in the presence of plasma. This was evidenced by the disappearance of flat regions in the electron temperature profile obtained by Thomson scattering. This island behavior depended on the magnetic configuration in which the plasmas were produced. DOI: 10.1103/PhysRevLett.87.135002 PACS numbers: 52.55.HcExistence of a set of nested magnetic surfaces (magnetic configuration) is a prer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 15 publications
0
29
1
Order By: Relevance
“…Energy confinement in LHD has ranged beyond twice the ISS-95 expectation [8,9] even at high <b> [7,10], and has no apparent dependence on heating method [11]. The enhanced confinement is attributed to an edge temperature pedestal [12,13,14], which is not generally observed in other stellarators but is not attributed to an H-mode in LHD. The pedestal may be associated with a chain of magnetic islands at or near the plasma edge [12], while avoidance of island chains at low order rational i values is associated with H-modes in W7-AS [15,16].…”
Section: -5mentioning
confidence: 85%
“…Energy confinement in LHD has ranged beyond twice the ISS-95 expectation [8,9] even at high <b> [7,10], and has no apparent dependence on heating method [11]. The enhanced confinement is attributed to an edge temperature pedestal [12,13,14], which is not generally observed in other stellarators but is not attributed to an H-mode in LHD. The pedestal may be associated with a chain of magnetic islands at or near the plasma edge [12], while avoidance of island chains at low order rational i values is associated with H-modes in W7-AS [15,16].…”
Section: -5mentioning
confidence: 85%
“…Recent Large Helical Device experiments show that the transport modeling based only on the fluid description is not sufficient for expressing transport phenomena in/around magnetic islands formed at the edge. For example, it is observed that an m/n = 1/1 magnetic island, which is formed at the edge by using external coils, is healed [1][2][3][4], where m and n are the poloidal and toroidal mode numbers respectively, and in the experiments the island temperature is 500 eV and the island density ∼ 10 19 m −3 . The island width depends on plasma pressure in the edge region, i.e., the width reduces as the pressure increases.…”
Section: Introductionmentioning
confidence: 98%
“…[9][10][11] Additionally, analytical island theories have been proven useful to interpreting experimental data of magnetic island dynamics in stellarators. [12][13][14] In the majority of these studies, however, an assumption of equilibration along magnetic field lines B Á $p ¼ 0 is employed. In the current work, the analytic theory of pressure-induced magnetic islands in 3-D equilibria is revisited, where the rigid requirement of parallel equilibration along field lines is weakened by allowing for the presence of finite, but large, parallel heat conduction.…”
Section: Introductionmentioning
confidence: 99%